DESIGN OF INFORMATION SYSTEMS IN SUPPLYING CARS CAR RENT'S FIRAS - Hisyam Hisyam; Eko Hadiyanto, SSI, MM Eko Hadiyanto, SSI, MM (Jurnal Sistem Informasi, 1997)
How important a computer device in the handle and one of the many problems withinthe system providing the one car. By using computers to provide information directlyto customers about the existence of the car. The design of this system did not rule tobe applied by other rental companies who want to develop his company.